Haemangioma left pinna with extensive, multiple skin ulcerations (Bangladesh Journal of Otorhinolaryngology, 2010)
Hemangioma is a benign vascular tumours constitute 7% of all benign tumours arise fromarterioles, venules & capillaries. It is deep red or blue-purple in colour, blench on pressure.Usually it is small & of no consequence is seen in isolation, but few may be multiple and /orpart of a wider syndrome. It is prone to extenssive bleeding if wall is damaged. It is besttreated with cryosungery or laser or if so large then by ligation or embolization of the feedingvessels. Here we have encountered a case of haemangioma in the left pinna with extensiveand multiple ulcerations of the skin, which is not so common site for development.Key words: Hemangioma; pinna.DOI: 10.3329/bjo.v16i1.5785Bangladesh J Otorhinolaryngol 2010; 16(1): 70-72